Breeding efficiency and optimum levels of various reproductive traits in Surti buffaloes - Shashidhara, T; Bhatia, S S; Appannavar, M M (The Indian Journal of Animal Sciences, 2012)
Records pertaining to 893 lactations of Surti buffaloes maintained at University of Agricultural Sciences, Dharwad, Karnataka, were utilized. The phenotypic correlations of breeding efficiency (BE) with age at first calving (AFC), first service period (FSP), first dry period (FDP) ,first lactation milk yield (FLMY), milk yield per lactation length (MY/FLC) and lifetime milk yield (LTMY) were -0.644, -0.499, -0.262, -0.363, -0.132 and -0.163, respectively. Phenotypic correlations were highly significant. Three prediction equations for BE obtained considering AFC and CI individually and in combination showed AFC was better determinant of BE compared to CI. The levels of AFC (1301 - 1390 days), FSP (61-90 days), FDP (91-150 days) were optimum for more milk production.